A minor tyrosine phosphorylation site located within the CAIN domain plays a critical role in regulating tissue-specific transformation by erbB kinase. - Chang, C M (1995)
Avian c-erbB encodes a protein that is homologous to the human epidermal growth factor receptor. Truncation of the amino-terminal, ligand-binding domain of this receptor results in an oncogene product which is a potent inducing agent for erythroleukemias but not fibrosarcomas in chickens. Here we show that mutation of a single tyrosine residue, p5, in the carboxyl terminus of the erbB oncogene product allows it to become sarcomagenic in vivo and to transform fibroblasts in vitro. Mutations of other autophosphorylation sites do not generate comparable effects. The increased transforming activity of the p5 mutant is accompanied by an elevated level of mitogen-activated protein kinase phosphorylation. By analogy to the human epidermal growth factor receptor, p5 is a minor autophosphorylation site and is located in a domain known to be involved in regulating calcium influx and receptor internalization (CAIN domain). This area of the erbB product has been found to be repeatedly deleted in various sarcomagenic avian erythroblastosis virus isolates. We precisely deleted the CAIN domain and also made point mutations of the acidic residues within the CAIN domain. In both cases, fibroblast-transforming potential is activated. We interpret these data to mean that p5 and its surrounding region negatively regulate fibroblast-transforming and sarcomagenic potential. To our knowledge, this represents the first point mutation of an autophosphorylation site that activates erbB oncogenicity.